PESAN KOMUNIKASI DALAM PENGGALANGAN DANA MELALUI WEBSITE - Intyaswati, Drina (Universitas Negeri Yogyakarta, 2016)
A website is widely used as a means of fundraising (fundraiser). The purpose of this study was to determine how the communication message conveyed in fundraising efforts through media website. By taking samples of the two types of websites as Fundraiser, wanted to also see each similarities and differences in communication strategies do. The analysis used is content analysis which analyzes the results of observations of the website Kitabisa.com and GandengTangan.org. Thus this type of research is qualitative descriptive. In conclusion there are similarities in general body of the message from both the website, there are differences in the nature of fundraising, and different from the long campaign period.Media website banyak digunakan sebagai sarana penggalangan dana (fundraiser). Tujuan dari penelitian ini adalah untuk mengetahui bagaimana pesan komunikasi yang disampaikan dalam usaha penggalangan dana melalui media website. Dengan mengambil sampel dua jenis website sebagai Fundraiser juga dilihat masing-masingpersamaan dan perbedaan dari strategi komunikasi yang dilakukan. Analisis yang digunakan adalah analisis isi,yang menganalisishasil observasi dari website Kitabisa. com dan GandengTangan.org. Dengan demikian jenis penelitian ini adalah kualitatif deskriptif. Kesimpulannya secara umum terdapat persamaan isi pesan dari kedua website tersebut, perbedaannya terdapat pada sifat penggalangan dana, serta berbeda pada lama masa kampanye.